ADVANCING HUMAN ANATOMY INSTRUCTION: ADDRESSING CONTEMPORARY CHALLENGES AND PEDAGOGICAL INNOVATIONS AT A CENTRAL ASIAN MEDICAL UNIVERSITY - Oltinbek Yuzboyev Abdullajon ugli (Modern American Journals, 2026)
Human anatomy remains a fundamental component of medical education. Despite its importance, the subject continues to face substantial pedagogical challenges. These include overreliance on traditional didactic lectures, inadequate integration of clinical relevance, and limited use of modern technological tools. This study, conducted at Central Asian Medical University, aimed to explore these challenges and evaluate the efficacy of integrative and technologically enhanced teaching methods. By analyzing student feedback and academic performance, the study found a significant preference and improved outcomes in modules employing active learning and digital tools such as 3D anatomy applications and virtual dissection platforms. The findings underscore the urgent need for curricular reform and investment in educational innovations.
Keywords: Anatomy education, medical pedagogy, active learning, 3D visualization, virtual dissection, curriculum reform, medical students.